Persepsi Risiko dan Sikap Toleransi Petani terhadap Keputusan Investasi Kelapa Sawit di Kecamatan Jelimpo Kabupaten Landak - Nelyanti, Oktavia; Fitrianti, Wanti; Maswadi, Maswadi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The development of the palm oil industry has had a significant impact on the regional economy, particularly in West Kalimantan. Palm oil industry has become one of the pillars of the economy in West Kalimantan because it has the potential to support land. This investment plays an important role in economic growth, because it can increase the growth rate and income of farmers, especially in Jelimpo District. However, investment activities are inseparable from risks that can cause losses. Seeing investment activities that are inseparable from risks, making decisions before starting an investment is very necessary. The purpose of the study, was to analyze the risk perception and tolerance of farmers towards palm oil investment decisions in Jelimpo District, Landak Regency. The method used in this study is quantitative descrptive. This study was conducted in Angan Tembawang Village and Kayu Ara Village, Jelimpo District, Landak Regency, with 86 sample respondents representing palm oil farmers. The variables in this study were divded into 3 (three), namely risk perception, tolerance and investment decisions. The two-tailed risk perception and tolerance attitude scores for the Spearman rank test were 0.000 and 0.005, respectively, due to the significance level (Sig).(2-tailed) 0.05 indicates that farmers' attitudes toward risk and their level of tolerance influence their choices about palm oil investments. While the correlation coefficient value of risk perception of 0.382 and farmer tolerance attitude of 0.302 means that the level of relationship between variables has a sufficint relationship. The results of the study showed that farmer perception of risk is in the high category, meaning that farmers consider palm oil investment as a farming activity that is full of threats and potential losses. While the farmer tolerance attitude towards risk is in the medium category or has a risk neutral attitude, meaning that farmers have a neutral attitude towards risk and tend to consider potential risks and benefits in a balanced manner when making investment decisions.